Analisis Tindak Tutur Direktif dalam Daftar Putar Kok Bisa Explains: Your Introduction to Science pada Channel Youtube Kok Bisa? (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2026)
Pragmatics is an aspect of linguistics that examines the relationship between external context and the purpose of an utterance. Context plays a crucial role in understanding a speaker's intent when communicating with their interlocutor. This study aims to collect, analyze, and discuss various expressions found in educational playlist videos on the YouTube channel "Kok Bisa." In academia, this study can bridge thinking, understanding, and perspectives on analyzing directive speech acts. The results of this study can provide additional insight into understanding directive speech acts. The approach used in this study is descriptive research. This study chose a pragmatic approach because it aligns with the topic of the study, namely related to speech acts and pragmatics. This study also uses listening and speaking techniques to collect and gather data. This study will discuss directive speech acts, so the pragmatic approach is the best choice for studying directive speech acts. A detailed analysis of the videos in this playlist shows that the application of directive speech acts plays a vital role in digital educational communication as a method for conveying messages and interacting between the sender and the audience. The findings of this study are expected to be a reference for future researchers who will conduct similar research, help educators in designing interactive and interesting learning communications, and foster critical awareness of media users regarding the function of language in digital communication.